Do oil and natural gas prices affect carbon efficiency? Daily evidence from China by wavelet transform-based approaches - Liu, Haiying; Pata, Ugur Korkut; Zafar, Muhammad Wasif; Kartal, Mustafa Tevfik; Karlilar, Selin; Caglar, Abdullah Emre (Elsevier Sci Ltd, 2023)
This study analyzes the impacts of oil and natural gas prices on China's carbon efficiency using wavelet transform-based time series methods. To this end, the study applies the continuous wavelet transform (CWT), wavelet transform coherence (WTC), and a time-varying wavelet causality test (TVWCT) to daily data during the period from October 31, 2012 to November 3, 2022. The CWT results show that there are volatilities in oil prices due to the coronavirus 2019 (COVID-19) pandemic, in natural gas prices because of the Russia-Ukraine war, and in carbon efficiency resulting from the Paris Climate Agreement. The WTC results demonstrate that increasing oil prices promote carbon efficiency in the 2014-2016 and 2018-2020 periods, while natural gas prices have a weak impact on carbon efficiency in 2022. Moreover, the TVWCT results prove that there is a strong causality leading from oil and natural gas prices to carbon efficiency in the long run. These results highlight that China can use volatilities in oil and natural gas prices as a policy tool to enhance carbon efficiency.
Keywords: Carbon efficiency; Oil prices; Natural gas prices; China; Wavelet-based methods